A Close-Up Look at the Natural World of a Pond - Taylor, Barbara (USA, 1992)
Examine the variety of life found in ponds, including the common newt, stickleback, and great diving beetle...
Keywords: Juvenile Non-Fiction; Nature; Pond Life & Animals; Ponds